On the mapping of especially valuable agricultural lands - I. Yu. Savin; A. P. Psareva (Бюллетень Почвенного института им. В.В. Докучаева)
Delineation of especially valuable agricultural lands (EVAL) is currently an important task, which will make it possible to preserve agricultural land for its direct use. There are currently no uniform approaches for delineation of EVAL, or they need to be upgraded. We have proposed a new approach based on GIS modeling and simulation of agricultural plant growth. It is proposed to delineate EVAL for each municipal district taking into account its existing specialization in agricultural production. The allocation of EVAL should be based on the assessment of potential productivity of soils and lands for cultivation of the main crops in the district. EVAL should also include pilot fields and areas used for scientific and educational purposes, regardless of potential soil productivity. The proposed approach has been successfully tested on the example of Yasnogorsk district of Tula region. It is shown that the EVAL map, based on the proposed approach, is more related to the actual land productivity and does not depend on the current land use within the area. It is possible to build an EVAL map for the whole country only by building such maps separately for all municipal districts of Russia.